Gestation-specific vital sign reference ranges in pregnancy - Green, L; Mackillop, L; Salvi, D; Pullon, R; Loerup, L; Tarassenko, L; Mossop, J; Edwards, C; Gerry, S; Birks, J; Gauntlett, R; Harding, K; et al. (Lippincott, Williams and Wilkins, 2020)
Objective: To estimate normal ranges for maternal vital signs throughout pregnancy, which have not been well defined in a large contemporary population.